Optimizing Zakat: A Multidisciplinary Analysis of Zakat Utilization for Enhancing Inclusive Education - Fitriani, Ely; Mudlofir, Ali; Doloh, Nurisan (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Observing global experiences and successes can provide valuable insights and open opportunities for mutual learning and adopting best practices in utilizing zakat to support inclusive education programs. The objectives of this research encompass a thorough analysis of the implementation and impact of zakat utilization in enhancing access, participation, and quality of education for students with special needs. The aim is to contribute to a better understanding of the potential of zakat as an inclusive financial instrument in improving the education sector. This research employs a qualitative research method with a literature-based approach, drawing from books and journal articles that present research findings on the utilization of zakat in education, particularly focusing on enhancing inclusive education. The findings of this research indicate that the potential of zakat as a financial solution can be relied upon to support inclusive education. The utilization of zakat holds positive value, including the development of inclusive facilities and the enhancement of educational accessibility. The syntax for optimizing zakat for the improvement of inclusive education includes identifying optimal funding sources, strategically allocating funds, implementing transparent and accountable management mechanisms, collaborating with educational institutions and relevant stakeholders, continuous monitoring and evaluation, and educating the community about the philosophy of zakat.